Idea neutralności pieniądza a wybrane nurty ekonomii - Mikołajczak, Dawid (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The history of the idea of neutrality of money begins with David Hume. There are at least five types of money neutrality. They could be grouped into neutrality relating to the moment (static neutrality and institutional neutrality) and neutrality relating to the period (dynamic neutrality, superneutrality, monetary neutrality). In mainstream economics, views on neutrality have changed over the years. Monetarism has differentiated views on the neutrality of money. The Austrian school remains sceptical about this simplification of the monetary economy. The theory of the real business cycle accepts any kind of neutrality in the period, and neutrality at the moment is not an important issue for it. Keynesianism focuses on neutrality in the short term and is sceptical about it.
Keywords: neutralność pieniądza; monetaryzm; keynesiści; austriacka szkoła ekonomii